REORIENTASI KAJIAN USHULUDDIN DALAM MERESPONS TANTANGAN ZAMAN - Muhyar Fanani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2014)
This paper attempts to discuss the various issues on the Islamic theology sciences. As implied in its name, ushuluddinsciences should be the core and kernel of Islamic sciences. In fact, the muslim community were far a way from theushuluddin sciences. It is caused that the theories in ushuluddin sciences are always referring to a past era and wasrarely associated with contemporary social problems. The efforts to develop the Islamic sciences are supposed to leave inadvance of the ushuluddin sciences. This paper intends to study the direction of the study sciences ushuluddin inresponse to the challenges of the times. If the ushuluddin sciences want to continue to exist, then the first thing that musttobe done is to change the scientific paradigm shift from which only oriented itself into a community-oriented.